1982
DOI: 10.1055/s-2008-1059617
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Central Myelinopathy in Cockayne's Syndrome. Report of 3 Siblings

Abstract: Three siblings with Cockayne's syndrome are reported. Sural nerve biopsies revealed segmental de- and remyelination with onion-bulb formation. Disturbed visual and brain-stem auditory evoked responses indicated demyelination of the central nervous system. The peripheral and central myelinopathy increased with age, suggesting a progressive disorder. Our observations support the theory of Cockayne's syndrome being a leukodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…These findings are compatible with the changes previously described in CS and support the hypothesis that CS is a form of leukodystrophy [3,4], Nystagmus has been reported previously in CS [4-6, 9], but its nature has not been sufficiently described. Cok er et al [9] reported horizontal pendular and gaze-evoked nystagmus in CS patients and attributed them to cerebel lar and brainstem demyelination.…”
Section: Vestibular Findings In Cockayne's Syndromesupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are compatible with the changes previously described in CS and support the hypothesis that CS is a form of leukodystrophy [3,4], Nystagmus has been reported previously in CS [4-6, 9], but its nature has not been sufficiently described. Cok er et al [9] reported horizontal pendular and gaze-evoked nystagmus in CS patients and attributed them to cerebel lar and brainstem demyelination.…”
Section: Vestibular Findings In Cockayne's Syndromesupporting
confidence: 82%
“…This syndrome is neuropathologically interpreted as a type of leukodystrophy [3,4], Hearing disorder is one of the characteristic features of CS, and the results of audiological tests including puretone audiometry, tympanometry and auditory brainstem responses have been reported [4][5][6], In contrast, reports on the vestibular functions in CS are rare. We performed the damped-rotation test [7] to evaluate the vestibuloocular reflex (VOR) in 2 siblings with CS, one of whom was also examined neuropathologically.…”
Section: Introductionmentioning
confidence: 99%
“…They typically interfered with fine motor skills and made patients prone to tripping and falling. In the literature, seven studies described 10 adults or older children with tremors [Kennedy et al, 1980;Smits et al, 1982;Fryns et al, 1991;Miyauchi et al, 1994;Inoue et al, 1997;Ellaway et al, 2000;Rapin et al, 2006].…”
Section: Fig 2 Patient 2 Very Mildmentioning
confidence: 97%
“…IQs in the mild group have been measured in the borderline range (70,74,75,77,78) [Kennedy et al, 1980;Smits et al, 1982;Miyauchi et al, 1994]. Survey data and the literature indicate that IQ declines as the syndrome progresses [Smits et al, 1982].…”
Section: Fig 2 Patient 2 Very Mildmentioning
confidence: 98%
See 1 more Smart Citation